2020
DOI: 10.2147/ndt.s270614
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA MEG3 Reduces Hippocampal Neuron Apoptosis via the PI3K/AKT/mTOR Pathway in a Rat Model of Temporal Lobe Epilepsy</p>

Abstract: Purpose Temporal lobe epilepsy (TLE) is a common neurological disorder, which is characterized by recurrent spontaneous seizures. Exploring the mechanisms of epileptogenesis has been considered as a priority. The aim of this study is to investigate the effects of LncRNA MEG3 in spontaneous recurrent epileptiform discharges (SREDs) and rats with TLE. Methods Rat model of TLE was produced by intraperitoneal injection of lithium chloride and pilocarpine. Rat hippocampal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…For instance, CDKN2B-AS1 was reported to up-regulate the expression of GDNF and inhibit neuronal apoptosis by acting as the molecular sponge for miR-133 ( Jiang et al, 2021 ). In addition, the expression of MEG3 was down-regulated in rats with TLE, and overexpression of MEG3 reduced the release of proinflammatory cytokines (including IL-1β, IL-6, and TNF-α) and inhibited neuronal apoptosis via the PI3K/AKT/mTOR pathway in the hippocampus ( Zhang et al, 2020 ). UBA6-AS1 might regulate cell proliferation and apoptosis by competitively binding to miR-7648 and targeting YTHDC1 ( Zheng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CDKN2B-AS1 was reported to up-regulate the expression of GDNF and inhibit neuronal apoptosis by acting as the molecular sponge for miR-133 ( Jiang et al, 2021 ). In addition, the expression of MEG3 was down-regulated in rats with TLE, and overexpression of MEG3 reduced the release of proinflammatory cytokines (including IL-1β, IL-6, and TNF-α) and inhibited neuronal apoptosis via the PI3K/AKT/mTOR pathway in the hippocampus ( Zhang et al, 2020 ). UBA6-AS1 might regulate cell proliferation and apoptosis by competitively binding to miR-7648 and targeting YTHDC1 ( Zheng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…AKT, also known as protein kinase B, is an important targeted kinase downstream of PI3K. This pathway is closely related to neuronal survival because many neurotrophic factors play a protective role in the brain by activating the pathway, thus inhibiting apoptosis [ 22 ]. Similar to our findings, a previous study showed that dexmedetomidine improved propofol-induced neuronal injury in rat hippocampus through the PI3K/Akt pathway [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lithium induces Bcl-2 transcription in retinas. Bcl-2 is a main controller for the regulation of both neural survival and axonal regeneration [ 131 ]. Moreover, the mechanism of Bcl-2 control of apoptosis [ 132 ].…”
Section: Lithium and Aaps In Glaucomamentioning
confidence: 99%